2013
DOI: 10.2459/jcm.0b013e32834a13c1
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Polyunsaturated fatty acids for the prevention of postoperative atrial fibrillation

Abstract: In conclusion, the results of the present meta-analysis of randomized controlled trials suggest that preoperative n-3 PUFA therapy may not reduce POAF in patients undergoing cardiac surgery. However, several aspects may have influenced this negative result, which need to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 11 publications
1
10
0
2
Order By: Relevance
“…In turn, the unsuccessful studies showed a higher EPA/DHA ratio. This view is supported by a recent study reporting a trend toward a benefit from n −3 PUFA supplementation when the EPA/DHA ratio is 1/2 (Benedetto et al, 2011). However, more mechanistic studies to ascertain the molecular basis of these effects are still lacking.…”
Section: Prevention Of Postoperative Atrial Fibrillationmentioning
confidence: 70%
“…In turn, the unsuccessful studies showed a higher EPA/DHA ratio. This view is supported by a recent study reporting a trend toward a benefit from n −3 PUFA supplementation when the EPA/DHA ratio is 1/2 (Benedetto et al, 2011). However, more mechanistic studies to ascertain the molecular basis of these effects are still lacking.…”
Section: Prevention Of Postoperative Atrial Fibrillationmentioning
confidence: 70%
“…[102][103][104] Multiple randomized clinical trials have been performed since to assess the efficacy of fish oil in reducing AF after heart surgery. [105][106][107][108][109][110][111] Because of inconclusive results, a series of recent meta-analyses have been performed to test for a definite therapeutic effect of this intervention. 107-111 The 5 metaanalyses to date have yielded different conclusions, although the latest pair have both suggested that PUFA in fish oils significantly decreases the risk of AF after cardiac surgery.…”
Section: Fish Oilmentioning
confidence: 99%
“…107-111 The 5 metaanalyses to date have yielded different conclusions, although the latest pair have both suggested that PUFA in fish oils significantly decreases the risk of AF after cardiac surgery. [107][108][109][110][111] Given the recent positive meta-analysis, larges adequately powered multicenter randomized trials are indicated to evaluate the safety and efficacy of fish oil for prevention of AF after cardiac surgery.…”
Section: Fish Oilmentioning
confidence: 99%
“…He et al . concluded that n ‐3 PUFA supplementation could significantly reduce the incidence of AF after heart surgery, but had no significant effect on its recurrence, while others did not observe any favourable effect ,. The lack of effect of n ‐3 PUFA supplementation on post‐operative AF has been recently confirmed by the OPERA trial in 1516 patients .…”
Section: Discussionmentioning
confidence: 99%